Neonatal resuscitation in Eastern Africa: health care providers' level of knowledge and its determinants. A systematic review and meta-analysis - Addis Eyeberu; Elias Yadeta; Deribe Bekele Dechasa; Ahmedin Aliyi Usso; Faysal Mohammed; Adera Debella (Global Health Action)
Background Even though effective neonatal resuscitation prevents the consequences of neonatal death related to birth asphyxia, a significant portion of healthcare personnel lacked understanding or performed it inconsistently. It is critical to have a comprehensive study that demonstrates the overall level of knowledge of healthcare providers regarding neonatal resuscitation in Eastern Africa. Methods Articles were searched from Science Direct, JBI databases, Web of Sciences, PubMed, and Google Scholar. The primary outcome was the level of knowledge of health care providers regarding neonatal resuscitation. Data were analyzed using Stata version 18 statistical software. The overall estimates with a 95% confidence interval were estimated using a random effect model. Results In this meta-analysis study, 7916 healthcare providers were included. The overall level of knowledge on neonatal resuscitation among healthcare providers in Eastern Africa was 59% [95% CI: 48–70]. Trained health care providers (OR = 3.63, 95% CI: 2.26, 5.00), and work experience of 5 years and above (OR = 2.08, 95% CI: 1.00, 3.16) were determinants of the level of knowledge. However, the level of education and availability of equipment were found to be insignificantly associated with the level of knowledge. Conclusions The results of this meta-analysis showed that healthcare professionals in Eastern Africa lacked sufficient knowledge about neonatal resuscitation. Having 5 years of work experience and training in neonatal resuscitation was found to be strongly associated with knowledge level. Thus, continuing education, training courses, and frequent updates on neonatal resuscitation protocols are required for healthcare professionals.